1979
DOI: 10.1016/0304-3959(79)90122-2
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of the spinal transmission of nociceptive information by supraspinal stimulation in the cat

Abstract: In cats anaesthetized with alpha-chloralose or sodium pentobarbitone a study was made of the effects of supraspinal electrical stimulation on the excitation of dorsal horn neurones by noxious and non-noxious cutaneous stimuli. Stimulation near the dorsal raphe of the midbrain non-selectively reduced the responses of neurones to both noxious and non-noxious stimuli. Intravenous naloxone (0.3-0.6 mg/kg) had no effect on this inhibition. Electrical stimulation near the medullary raphe selectively reduced the exci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
22
0

Year Published

1980
1980
2006
2006

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 153 publications
(22 citation statements)
references
References 38 publications
0
22
0
Order By: Relevance
“…Previous studies have demonstrated that electrical and chemical stimulation of the RVM or NRM result in an inhibition of spinal nociception (Fields et al, 1977;Belcher et al, 1978;Duggan and Griersmith, 1979;Rivot et al, 1980;Carstens et al, 1981;Hodge et al, 1983;Light et al, 1986;Zhuo and Gebhart, 1997). The mechanism of the antinociceptive effect is controversial, however, because many neurotransmitters in addition to 5-HT exist in raphe neurons that may contribute to the descending modulation of spinal sensory systems (e.g., GABA, glycine, acetylcholine, somatostatin, substance P, enkephalin, dynorphin, galanin, thyrotropin-releasing hormone, and cholecystokinin) (Millan, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that electrical and chemical stimulation of the RVM or NRM result in an inhibition of spinal nociception (Fields et al, 1977;Belcher et al, 1978;Duggan and Griersmith, 1979;Rivot et al, 1980;Carstens et al, 1981;Hodge et al, 1983;Light et al, 1986;Zhuo and Gebhart, 1997). The mechanism of the antinociceptive effect is controversial, however, because many neurotransmitters in addition to 5-HT exist in raphe neurons that may contribute to the descending modulation of spinal sensory systems (e.g., GABA, glycine, acetylcholine, somatostatin, substance P, enkephalin, dynorphin, galanin, thyrotropin-releasing hormone, and cholecystokinin) (Millan, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…These procedures include systemic and intrathecal morphine administration, dorsal column stimulation, transcutaneous electrical stimulation, stimulation of periaqueductal, periventricular and thalamic structures and heterotopic noxious stimulation. (ii) Secondly, these cells are strongly modulated by supraspinal structures; in particular electrical stimulation of the PAG induces marked inhibitory effects on dorsal horn convergent neurones (Guilbaud et al, 1972;Liebeskind et al, 1973;Oliveras et al, 1974;Duggan & Griersmith, 1979;Hayes et al, 1979;Carstens et al, 1980;Yezierski et al, 1982). Thus this type of neurone appears appropriate for an effect to be found following PAG morphine.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, stimulation of the following sites has resulted in the inhibition of Class 2 dorsal horn neurones: the mesencephalic periaqueductal gray [Oliveras, Besson, Guilbaud and Liebeskind, 1974], the medullary raphe nuclei [Oliveras, Redjemi, Guilbaud and Besson, 1975;Fields, Basbaum, Clanton and Anderson, 1977], the dorsal columns [Nashold and Friedman, 1972;Foreman, Beall, Applebaum, Coulter and Willis, 1976] and contralateral peripheral nerve [Taub, 1964;Price, 1972] and has produced analgesia in man or other animals. However, recent reports indicate that large doses of naloxone fail to antagonize the descending inhibition originating from the mesencephalic periaqueductal gray [Carstens, Klumpp and Zimmermann, 1979] or medullary raphe sites [Duggan and Griersmith, 1979]. Similarly in this report we have shown that naloxone fails in Class 2 neurones to antagonize inhibition of dorsal column or contralateral plantar origin.…”
Section: Discussionmentioning
confidence: 43%